Constructive coping strategies as predictors of positive mental health in young adults - Tarar, Farwa Yousaf; Akhtar, Nasreen (Journal of Pakistan Psychiatric Society, 2021)
OBJECTIVE                                                 The aim of present research was to study the relationship between constructive coping strategies and positive mental health (flourishing) among university students. It also aimed to investigate the predictive role of constructive coping strategies in determining positive mental health.STUDY DESIGNCorrelational research design was used for this research.PLACE AND DURATION OF STUDYThe study was conducted in HEC recognized public universities of Lahore during 2016-2017.SUBJECTS AND METHODSA sample of 223 undergraduate and postgraduate students with age range of 19 to 28 years was selected for research. Constructive coping strategies were measured by COPE Inventory and positive mental health was measured by flourishing scale.RESULTSThe results showed that, active coping, religious coping positive reinterpretation and growth, and use of instrumental social support were positively correlated with the positive mental health among students. Active coping was the strongest predictor of positive mental health followed by positive reinterpretation and religious coping. The females scored higher on religious coping strategy while males were higher on humor and social-support as coping strategies.CONCLUSION Active coping, religious coping, positive reinterpretation and social support were helpful in enhancing positive mental health among university students. Females made greater use of religious coping strategy whereas males employed humor as coping strategy.The study has important implications in student counselling. It implies how coping can enhance subjective positive mental health among students.